Regional Carbon Pricing for International Maritime Transport : Challenges and Opportunities for Global Geographical Coverage - Dominioni, Goran; Heine, Dirk; Martinez Romera, Beatriz (World Bank, Washington, DC, 2018)
Although the existing literature identifies a fuel levy imposed by means of a global agreement as the most efficient policy for carbon pricing in the maritime sector, scholars and policy makers debate the possibility for regional measures to be introduced in case a global agreement cannot be achieved. This debate has highlighted several economic, legal, and political challenges that the implementation of an efficient and effective regional scheme would have to face. This paper compares the relative performance of various regional measures for carbon pricing based on the following criteria: jurisdictional basis, data availability, environmental effectiveness and avoidance strategies, impact on competitiveness, differentiation for developing countries, and incentives for reaching a global agreement. The main finding is that, if carefully designed, a cargo-based measure that covers the emissions released throughout the whole voyage to the cargo destination presents various advantages compared with other carbon pricing schemes. These advantages have been largely ignored in the literature.